From Doctor to Becoming a Patient and then Regaining my Identity as a Physician - Maeirah Shafique (Pakistan Armed Forces Medical Journal, 2026)
Doctors are a special breed amongst human beings. Once we join this profession, it resets our entire personality. From a simple human, we are gradually molded into one with nerves of steel. We are trained to recognize symptoms, interpret investigations, formulate differentials and reassure not only anxious patients but also their entire families. We can undergo the most horrific experiences as we diagnose and battle with various threats to humanity. We learn to maintain composure when others are frightened. Yet when the tables are turned and one finds oneself sitting opposite another treating physician or staring up at the Operation theatre ceiling, the familiar territory of medicine can suddenly feel very different. Myasthenia gravis is a chronic autoimmune disorder characterized by antibody formation against the acetylcholine receptors on neuromuscular junctions resulting in fluctuating weakness and fatigability.1 It is commonly referred to as snowflake disease due to extreme variations and every person’s experience with the condition is completely unique. For the physician who lives with it, however, the diagnosis encompasses much more than neuromuscular transmission. The most profound aspect of a fluctuating illness is its invisibility! A patient may appear completely well during one encounter and struggle considerably at another without any obvious external sign.2